Kurikulum Komunikasi dan Jurnalistik Dakwah Perbandingan dan Rekomendasi Pembaruan - Masduki, Masduki; Masduki (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
This paper attempts to elaborate on the current existence of the Islamic Communication curriculum, particularly Dakwah Journalism as one of the Islamic communication education pillars, either on state or private Islamic universities in Indonesia. Departing from an explanation of the empirical phenomenon of the technological revolution and globalization of communication that brought significant impacts on the communication industry and social-global behavior, this paper wants to criticize backwardness content of DakwahJournalism curriculum that failed to adopt both dynamics as a genial formulation to form new scholar competency of Islamic Communications in the modern world. The curriculum focus for journalism ethical values only shows another fact that there is a weakness in the scientific exploration of the journalism science in Islamic tradition. This paper will be concluded with my analysis for the differences of vision and mission addressed by Islamic Communication Departments (KPI) in PTAI that aggravate the above conditions. This problem represents only one example of the complexity of the problems in the PTAI teaching system amidst of migration policy from IAIN into State Islamic University(UIN). To establish competitive graduates with holistic competency, it is necessary for PTAI managers to develop a new framework, vision, mission, and curriculum content at large. The initiatives can be started by changing the Dakwah Journalism curriculum.